2018
DOI: 10.3389/fpls.2018.01184
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies for Dynamic Plant Height and Number of Nodes on the Main Stem in Summer Sowing Soybeans

Abstract: Plant height (PH) and the number of nodes on the main stem (NN) serve as major plant architecture traits affecting soybean seed yield. Although many quantitative trait loci for the two traits have been reported, their genetic controls at different developmental stages in soybeans remain unclear. Here, 368 soybean breeding lines were genotyped using 62,423 single nucleotide polymorphism (SNP) markers and phenotyped for the two traits at three different developmental stages over two locations in order to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 63 publications
(87 reference statements)
8
54
0
Order By: Relevance
“…Although MSN is an important plant architecture trait, there have not been many reports involving the trait. After a careful search of SoyBase (http://soybase.org) and journals, altogether 65 MSN QTLs were published in 12 reports, each with 1–14 QTLs, including those identified from biparental populations, such as recombinant inbred line (RIL) populations, and those identified from germplasm populations (Chang et al., 2018; Chen et al., 2007; Fang et al., 2017; Gai, Wang, Wu, & Chen, 2007; Li, Sun, Han, Teng, & Li, 2010; Liu, Li, Fan. et al., 2017; Liu et al., 2011; Liu, Li, Hu, et al., 2017; Moongkanna et al., 2011; Wang et al., 2012; Yao et al., 2015; Zhang et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MSN is an important plant architecture trait, there have not been many reports involving the trait. After a careful search of SoyBase (http://soybase.org) and journals, altogether 65 MSN QTLs were published in 12 reports, each with 1–14 QTLs, including those identified from biparental populations, such as recombinant inbred line (RIL) populations, and those identified from germplasm populations (Chang et al., 2018; Chen et al., 2007; Fang et al., 2017; Gai, Wang, Wu, & Chen, 2007; Li, Sun, Han, Teng, & Li, 2010; Liu, Li, Fan. et al., 2017; Liu et al., 2011; Liu, Li, Hu, et al., 2017; Moongkanna et al., 2011; Wang et al., 2012; Yao et al., 2015; Zhang et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study and those found in the literature are different for the following reasons: Different mapping populations were used in different studies. Among the 12 reports, nine of used biparental populations with only 13 parents involved, whereas another three reports (Chang et al., 2018; Fang et al., 2017; Liu, Li, Fan, et al., 2017) used germplasm populations. The materials in the literature are mainly from later MGs than those in the present study. Different mapping procedures were used in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS is considered as a significant approach to study genetic variants in a large population as it saves time and cost of developing a bi-parental population, deduces multi-allelic variations to help identify the most favorable alleles of a target trait in a single analysis, and it is more powerful and easy to fine map QTL due to a higher resolution resulting from a high genetic diversity (Breseghello and Sorrells, 2006;Atwell et al, 2010). GWAS takes complete advantage of all the recombination events occurring in the evolution of a natural population (Chang et al, 2018). GWAS has been used to understand the genetic basis of complex traits in various plant and animal species (Hirschhorn and Daly, 2005;McCarthy et al, 2008;Ingvarsson and Street, 2011;Bush and Moore, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, most complex traits such as nutrient use efficiency are usually controlled by multiple loci, and thus MLM based models are never accurate to estimate the marker effects for such traits. Another problem with MLM based models is that the stringent criterion of significance for marker selection such as Bonferroni correction does not allow many significant markers to be detected Chang et al, 2018). Multi-locus mixed linear models have been developed to address this problem because they can be used to detect powerful marker-trait associations (MTA) using lower significance criterion as no Bonferroni correction is applied Chang et al, 2018;Lü et al, 2018;Ma et al, 2018;Peng et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation